1994
DOI: 10.1099/13500872-140-8-1917
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation of nitrogenase expression in Klebsiella pneumoniae

Abstract: An investigation into the influence of N, on the expression of Klebsiella pneumoniae nitrogenase has led to a reassessment of the role of the nitrogenase MoFe protein in autoregulation. Anaerobic derepression of nitrogenase (C,H,-reducing) activity, of Nif D and K polypeptides, and of nifH-/ac expression, following the removal of excess NH; , were greater under N, than Ar. This enhancement occurred in Nif+ but not in Nif-strains, and in Nif+ strains was prevented by CZH, , an inhibitor of N, fixation. Thus N, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In previous studies ( 12 , 18 , 45 ), the induction of nitrogenase activity in cells was performed under various N 2 gas phases; however, the optimal N 2 content has not yet been adequately examined. In order to establish optimal induction conditions for nitrogenase in Tl .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies ( 12 , 18 , 45 ), the induction of nitrogenase activity in cells was performed under various N 2 gas phases; however, the optimal N 2 content has not yet been adequately examined. In order to establish optimal induction conditions for nitrogenase in Tl .…”
Section: Resultsmentioning
confidence: 99%
“…In the case of heterocystous cyanobacteria such as Anabaena variabilis and Nostoc spongiaeforme , nitrogenase induction was stronger under the culture conditions of argon-based gas mixtures (Ar/CO 2 =99/1 [v/v%]) than N 2 -based gas mixtures (N 2 /CO 2 =99/1 [v/v%]) ( 45 ). In non-cyanobacteria, the nitrogenase activity of Klebsiella pneumoniae was weaker under the conditions of N 2 -based gas mixtures (N 2 /CO 2 = 99/1 [v/v%]) than argon-based gas mixtures (Ar/CO 2 = 99/1 [v/v%]) ( 12 ). These findings are consistent with our experimental results, suggesting that the N 2 concentration in culture medium significantly affected the induction of nitrogenase activity by the thermophilic cyanobacterium of Tl.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that the observation of a dramatic increase in nitrogenase activity on cell cultivation under N 2 is not unprecedented. For the K. pneumoniae wild‐type strain, it has been shown that the rate of nitrogenase synthesis is increased by a factor of ≈ 2.5 under N 2 compared with the rate obtained with serine‐grown cells under Ar [54].…”
Section: Resultsmentioning
confidence: 99%
“…In diazotrophs, nitrogenase synthesis is derepressed under conditions of nitrogen limitation. N 2 is not an inducer of nitrogenase synthesis, though sustained derepression of nitrogenase depends on active N 2 fixation in order to maintain general nitrogen status and thereby allow protein synthesis to continue [168]. In cyanobacteria that can fix N 2 aerobically, nitrogenase synthesis occurs in the presence of air.…”
Section: Nitrogenase In Non‐heterocystous Cyanobacteriamentioning
confidence: 99%